(untitled) - Casey, Thomas Aquinas (Philadelphia, Pennsylvania, 1984)
The book is divided into a number of major sections with each chapter almost a complete entity. The first group of chapters covers corneal anatomy, physiology and wound healing. Immunology and the ocular surface are also discussed. The next area is the factors involved in the operation itself: eye-banking, instruments, preoperative assessment, indications for full thickness and lamellar grafting and the techniques used. Ensuing chapters deal with the more complicated types of surgery and the advanced techniques needed. The book concludes with ideas for developing countries and thoughts for the future
Keywords: cornea; transplantation